2018
DOI: 10.2106/jbjs.17.00777
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effect of Low-Dose, Electromyography-Guided Botulinum Toxin A Injection in the Treatment of Chronic Lateral Epicondylar Tendinopathy

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 55 publications
0
21
0
3
Order By: Relevance
“…Often called the “tennis elbow,” lateral epicondylosis is a common painful condition that affects the tendons joining the forearm muscles on the outside of the elbow [ 146 ]. Common non-surgical treatment of lateral epicondylosis includes, but not is limited to, physiotherapy [ 147 ], injections of corticosteroid [ 148 ], extracorporeal shock wave therapy [ 149 ], acupuncture [ 150 ], topical glyceryl trinitrate [ 151 ], botulinum toxin [ 152 ], and platelet-rich plasma [ 153 ]. Regarding the cell therapy for lateral epicondylosis, it was surprising that only a handful of studies had been conducted to date.…”
Section: Type Of Msds Targetedmentioning
confidence: 99%
“…Often called the “tennis elbow,” lateral epicondylosis is a common painful condition that affects the tendons joining the forearm muscles on the outside of the elbow [ 146 ]. Common non-surgical treatment of lateral epicondylosis includes, but not is limited to, physiotherapy [ 147 ], injections of corticosteroid [ 148 ], extracorporeal shock wave therapy [ 149 ], acupuncture [ 150 ], topical glyceryl trinitrate [ 151 ], botulinum toxin [ 152 ], and platelet-rich plasma [ 153 ]. Regarding the cell therapy for lateral epicondylosis, it was surprising that only a handful of studies had been conducted to date.…”
Section: Type Of Msds Targetedmentioning
confidence: 99%
“…Injektion verweisen wir auf eine weitere neue Studie von Cogné et al [32]. In dieser Arbeit wurde die Studie der Arbeitsgruppe aus dem Jahr 2018 [17] fortgeführt: Die 29 Probanden der Therapiegruppe mit primär erfolgter Botu-linumtoxininjektion und die 21 Probanden der Kontrollgruppe mit nachträglicher Infiltration mit Botulinumtoxin in der beschriebenen Technik nach 90 Tagen (n = 48), 180-270 Tagen (n = 48) und nach einem Jahr (n = 24) wurden weiterverfolgt. Bei 22 der 50 Probanden stellte sich nach einer Injektion und bei weiteren 18 der 50 Probanden stellte sich nach einer 2.…”
Section: Schlussbetrachtungunclassified
“…In der Studie von Lin et al [15] mit 50 Einheiten Onabotulinumtoxin und einem Injektionsort relativ nah am Epicondylus humeroradialis zeigte sich wiederum bei allen Probanden der Botulinumtoxingruppe eine Abschwächung der Handextension und der Fingerextension bei den Kontrollen nach 4-8 Wochen. In der Studie von Creuzé et al [17]…”
Section: Dosisunclassified
See 1 more Smart Citation
“…Among the numerous injection modalities available, corticosteroid injection remains the mainstream of intra-articular treatment in lateral epicondylitis, and its effect can be augmented in a mix with lidocaine injection [ 3 ]. A recent study on botulinum toxin on ECRB under electromyographic (EMG) guidance revealed analgesic effect due to inhibited pain neurotransmission, and improved healing outcomes in tendon injury by a decrease in tension at the site of enthesis and an increase in muscular blood flow [ 14 ]. A recent meta-analysis concluded that autologous blood products (such as autologous blood and platelet-rich plasma) have an intermediate-term effect on pain relief and elbow function, as compared to corticosteroid injection that exerts a short term effect [ 15 ].…”
Section: Treatment Optionsmentioning
confidence: 99%